Study Of Divergence Of Go Public Company's Financial Performance Based On Website Before and After Merger Using Window Period Method Time Frame 2015 - 2017 - Wibowo, Ardy Indra Lekso; Putra, Aditya Dwiansyah; Dewi, Murni Sari; Radianto, Denny Oktavina (Pandawan, 2019)
This study aims to determine the differences in financial performance of website based companies (technopreneur) before and after merger determination using fundamental variables, namely CR (current ratio), DER (debt to equity ratio), ROA (return on assets), ROE (return on equity), and NPM (net profit margin) for all merger companies listed on the Indonesia Stock Exchange. This study uses an event study type with a window period of 1 year before and 1 year after the determination of a merger. The population of this study uses all website based publicly listed companies that merged on the Indonesia Stock Exchange in the period 2015 - 2017 with the sampling technique using purposive sampling technique so that 17 companies were sampled. This analysis technique uses a different test analysis on abnormally distributed data (Wilxocon signed rank test). The data source used is secondary data from the official IDX and KPPU websites